2018
DOI: 10.5114/jcb.2018.77948
|View full text |Cite
|
Sign up to set email alerts
|

Plan reproducibility of intraoperatively custom-built linked seeds compared to loose seeds for prostate brachytherapy

Abstract: PurposeFew studies have compared the implant quality of linked and loose seeds for prostate brachytherapy. This study aimed to evaluate and compare plan reproducibility of intraoperatively built custom linked seeds and loose seeds for prostate brachytherapy.Material and methodsBetween December 2010 and March 2014, 76 localized prostate cancer patients received Iodine-125 brachytherapy with external beam radiotherapy. Linked and loose seeds were implanted in 39 and 37 patients, respectively. The primary endpoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…In several studies, PV 150 and UD 30 were significantly lower and HI was significantly higher in the IBCL group than in the LS group, consistent with the results of the present study [ 7 , 11 ]. Two studies have reported that RV 100 was significantly lower in the IBCL group than in the LS group, but we found no significant difference in the present study [ 7 , 13 ]. We consider that the decrease in variation of dosimetric parameters and the reduction of high-dose areas in both the prostate and urethra are due to the following characteristics of IBCL seeds compared with LS: (i) reduction of seed migration and loss, (ii) suppression of unintentional movement within the prostate after seed implantation, (iii) correct distance between seeds due to use of spacers, and (iv) the ability to intentionally place the seeds outside the prostate, which is particularly useful in peripheral loading techniques, and contributes to reducing urethral dose.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In several studies, PV 150 and UD 30 were significantly lower and HI was significantly higher in the IBCL group than in the LS group, consistent with the results of the present study [ 7 , 11 ]. Two studies have reported that RV 100 was significantly lower in the IBCL group than in the LS group, but we found no significant difference in the present study [ 7 , 13 ]. We consider that the decrease in variation of dosimetric parameters and the reduction of high-dose areas in both the prostate and urethra are due to the following characteristics of IBCL seeds compared with LS: (i) reduction of seed migration and loss, (ii) suppression of unintentional movement within the prostate after seed implantation, (iii) correct distance between seeds due to use of spacers, and (iv) the ability to intentionally place the seeds outside the prostate, which is particularly useful in peripheral loading techniques, and contributes to reducing urethral dose.…”
Section: Discussioncontrasting
confidence: 99%
“…Several papers have reported no significant difference in PV 100 and PD 90 between the two groups [5,8,10]. Inada et al reported that PV 100 was significantly higher in the IBCL group than in the LS group, whereas other studies showed that PD 90 was significantly lower in the IBCL group than in the LS group [7,11,12,13]. In several studies, PV 150 and UD 30 were significantly lower and HI was significantly higher in the IBCL group than in the LS group, consistent with the results of the present study [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no clinical impact of this difference, but the follow-up was too short (especially in the IBCLS group) and the number of relapses too small to draw any conclusion. In a recent dosimetric study performed by Kaneda et al ., there was a trend towards a lower post-operative D 90 , V 150 , and V 100 with IBCLS compared to LS (118.8% vs. 127.2%; 51.7% vs. 66.7%; 0.44 ml vs. 0.61 ml, respectively, p < 0.01) [ 10 ]. Another retrospective study showed that procedures with LS were associated with intraoperative lower doses to the urethra and rectum compared to IBCLS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the reproducibility of dosimetric plan, the ΔD 90 , which is the absolute change in the minimum dose received by 90% of the prostate volume between the intraoperative and post-operative planning, was calculated (ΔD 90 = post-operative D 90 – intraoperative D 90 ). If the absolute change in prostate D 90 (ΔD 90 = post-operative D 90 – intraoperative D 90 ) is low, the plan reproducibility is considered to be high [ 10 ].…”
Section: Methodsmentioning
confidence: 99%